(untitled) (Research, Society and Development, 2022)
Urinary tract infection (UTI) is an important risk factor for pregnant women and the fetus, and is considered the most common form of bacterial infection during pregnancy. The study aimed to search the available literature for the relationship between urinary tract infection in pregnant women and prematurity. This is an integrative literature review study, using the controlled and uncontrolled descriptors in the Health Sciences (DeCS) descriptors. The online databases searched were: Latin American and Caribbean Health Literature and the online Medical Literature Analysis and Retrieval System, accessed through the Virtual Health Library Research Portal (BVS), as well as the Scientific Electronic Library Electronic Library Online. Data analysis was performed in a descriptive way of the content. The results showed that urinary tract infection is a factor of important complications during pregnancy, however it is not the only responsible for the increase in occurrences. Several of these complications can be avoided with an effective prenatal follow-up, if an early diagnosis improves clinical outcomes. In view of this, it has been recognized and discussed more frequently in the literature. However, it can be concluded that UTIs in gestational patients are common, especially those caused by Escherichia coli. There is an increase in premature birth in pregnant women due to high antibodies due to Escherichia Coli, maternal mortality also occurs, which can also be aggravated due to the risks of infections.